2012
DOI: 10.1002/bdrb.21019
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Interleukin‐6 Signal Blockade on Fertility, Embryo‐fetal Development, and Immunization In vivo

Abstract: Possible effects of interleukin‐6 (IL‐6) on reproductive performance, embryonal development, parturition, and postnatal development have been suggested based on protein/mRNAexpression level of IL‐6 in related organs, but less is known about functions of IL‐6 signals in these areas. Following two different approaches have been employed to investigate the role of IL‐6 signals in fertility and pre‐/postnatal development: administration of a rat anti‐mouse IL‐6 receptor antibody, MR16‐1, to mice as a neutralizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 61 publications
3
33
0
2
Order By: Relevance
“…Preclinical data from experimental animal studies suggest that blockade of IL-6-receptor signaling induces no apparent biological effects on fertility or pre-/postnatal development [6].…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical data from experimental animal studies suggest that blockade of IL-6-receptor signaling induces no apparent biological effects on fertility or pre-/postnatal development [6].…”
Section: Introductionmentioning
confidence: 99%
“…Yoshida et al reported that first intravenous dosing (2 mg/body) inhibited the production of antibodies to MR16-1 after repetitive intraperitoneal or subcutaneous injections of MR16-1 in NZB/NZW F1 mice29. Sakurai et al also suggested the possibility that tolerance induction would inhibit the production of antibody to drug after finding that antibodies to MR16-1 were detected in some mice treated with 15 mg/kg of MR16-1 intravenously every 3 days but not detected in 50 mg/kg groups30. In our study, however, in Il6ra +/+ -h IL6 transgenic mice expressing only mouse Il6ra, the same doses of tocilizumab produced extremely high titers of anti-tocilizumab antibodies, suggesting that there might be some other mechanism than tolerance induction from a first higher dosing.…”
Section: Discussionmentioning
confidence: 99%
“…Along with animal models, the available case reports and case series have yielded no evidence of teratogenic and/or mutagenic effects or an impact on fertility [96, 97]. An animal study showed an increased risk of spontaneous miscarriages and embryonic/fetal mortality in high doses [98].…”
Section: Other Biologicsmentioning
confidence: 99%